MASTER Real-Time Multi-Message Observations of High Energy Phenomena - Vladimir M. Lipunov; Viktor G. Kornilov; Kirill Zhirkov; Artem Kuznetsov; Evgenii Gorbovskoy; Nikolai M. Budnev; David A. H. Buckley; Rafael Rebolo Lopez; Miquel Serra-Ricart; Carlos Francile; Nataly Tyurina; Oleg Gress; et al. (Universe, 2022)
This review considers synchronous and follow-up MASTER Global Robotic Net optical observations of high energy astrophysical phenomena such as fast radio bursts (FRB), gamma-ray bursts (including prompt optical emission polarization discovery), gravitational-wave events, detected by LIGO/VIRGO (including GW170817 and independent Kilonova discovery), high energy neutrino sources (including the detection of IC-170922A progenitor) and others. We report on the first large optical monitoring campaign of the closest at that moment radio burster FRB 180916.J0158+65 simultaneously with a radio burst. We obtained synchronous limits on the optical flux of the FRB 180916.J0158+65 and FRB 200428 (soft gamma repeater SGR 1935+2154) (The CHIME/FRB Collaboration, Nature 2020, 587) at 155093 MASTER images with the total exposure time equal to 2,705,058 s, i.e., 31.3 days. It follows from these synchronous limitations that the ratio of the energies released in the optical and radio ranges does not exceed 4 × 105. Our optical monitoring covered a total of 6 weeks. On 28 April 2020, MASTER automatically following up on a Swift alert began to observe the galactic soft gamma repeater SGR 1935+2154 experienced another flare. On the same day, radio telescopes detected a short radio burst FRB 200428 and MASTER-Tavrida telescope determined the best prompt optical limit of FRB/SGR 1935+2154. Our optical limit shows that X-ray and radio emissions are not explained by a single power-law spectrum. In the course of our observations, using special methods, we found a faint extended afterglow in the FRB 180916.J0158+65 direction associated with the extended emission of the host galaxy.